Inventory of Collembola Species Around Ahmad Dahlan University Campus 4 And Its Surroundings - Hanifuddin, Afnan Saud; Kamalia, Lulu Atikah (Journal of Biotechnology and Natural Science, 2022)
Collembola has an important value for the environment as a bioindicator in maintaining the balance of the ecosystem. Land conversion in the UAD campus 4 area can reduce the diversity of Collembola. This study aims to find out the level of diversity of Collembola species that exist on campus 4 of UAD and its surroundings, and also find out which areas have the highest and lowest number of individuals. The research area for sampling in this study is the UAD 4 campus area, vacant land, housing and rice fields. Sampling was carried out as many as four repetitions. The collembola trapped in the pitfall trap is then moved in a microtube. The collembola that has been obtained is then identified up to the species level. The data obtained were analyzed by descriptive analysis. The types of collembola obtained at campus 4 UAD and its surroundings are Folsomia sp,, Isotoma sp., Isotomurus sp., Entomobrya sp., Sminthurus sp., Hypogatrusa sp, and Lepidocyrtus sp. The collembola species that is most commonly found are from Entomobrya famili with 106 individuals and the least individual from Sminthuridae famiili with 4 individuals.